The right to basic education for children with special education needs in South Africa - Matsaung, Potata Japhta (My University, 2025)
The right to education is guaranteed under section 29 of the Constitution of the Republic of South Africa (Act 108 of 1996). Notwithstanding this constitutional guarantee, children with special education needs face significant barriers in realising their right to education. The barriers they face include inadequate infrastructure, insufficient educator training, and challenges linked to policy implementation. This study investigated the realisation of the right to basic education for children with special needs in South Africa. It focused on the legislative and policy frameworks that promote inclusive education. The key questions that the study investigated are: To what extent do the provisions of the South African Schools Act 84 of 1996 comply with the constitutional obligation to guarantee the right to basic education for children with special education needs? What mechanisms are available to the state to best realise these rights in terms of the Constitution? Does the jurisprudence of the Constitutional Court and other superior courts affirm the immediate realisation of the right to basic education under section 29, particularly in relation to children with special education needs? The study utilised qualitative methodology, which involved a doctrinal analysis of primary sources, encompassing constitutional provisions, legislation, and case laws, alongside secondary sources like books, scholarly journal articles, policy documents, reports, government publications, the Education White Paper 6 of 2001, and statistical data. The key findings of this study revealed several significant shortcomings in the Schools Act regarding the provision of education for children with special education needs. The key issues identified included inadequate financial resources, a shortage of trained educators, and insufficient accessible infrastructure, all of which hinder the effective implementation of inclusive education. Furthermore, the state was found to have failed in fulfilling its constitutional obligations under section 29, due to the lack of accountability mechanisms, which hindered the provision of equal educational opportunities. The jurisprudence of the Constitutional Court affirmed the right to basic education as immediately realisable. However, the implementation of this constitutional right remains limited. The recommendations of the study address key areas where improvements are needed. For example, amendments to the Constitution, the Schools Act, and policy reforms.
Thesis (LLM.) -- University of Limpopo, 2025
Keywords: Basic education; Special education needs; Socio-economic rights; Resource constraints; Inclusive education; State; International Law; Basic education -- South Africa; Economic rights; Inclusive education -- South Africa; Children with disabilities; Special education -- South Africa; Special education -- Law and legislation -- South Africa